Solid-acid-based process for the conversion of hemicellulose - Dhepe, Paresh Laxmikant; Sahu, Ramakanta (Green Chemistry, 2010)
We describe a solid-acid-catalyzed conversion of hemicellulose (a component of lignocellulosic material) into xylose, arabinose and furfural in aqueous media.

One pot and single step hydrolytic process for the conversion of lignocellulose into value added chemicals - Dhepe, Paresh Laxmikant; Sahu, Ramakanta (WO2011092711 A1, 2011)
The present invention provides a single step hydrolytic process for the conversion of lignocellulose, into value added chemicals wherein said process is catalyzed by at least one heterogeneous solid acid catalyst selected from a group comprising of zeolites, zeolites with Si/metal, mesoporous silica, oxides and phosphates, clays, ion-exchange resins, heteropolyacids, various sulfates, phosphates, selenates, crystalline materials and amorphous materials.

One-Pot method for the selective conversion of hemicellulose from crop waste into C5 sugars and furfural by using solid acid catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Chemsuschem, 2012)
We present a solid-acid catalyzed one-pot method for the selective conversion of solid hemicellulose without its separation from other lignocellulosic components, such as cellulose and lignin. The reactions were carried out in aqueous and biphasic media to yield xylose, arabinose, and furfural. To overcome the drawbacks posed by mineral acid methods in converting hemicelllulose, we used heterogeneous catalysts that work at neutral pH. In a batch reactor, these heterogeneous catalysts, such as solid acids (zeolites, clays, metal oxides etc.), resulted in >90% conversion of hemicellulose. It has been shown that the selectivity for the products can be tuned by changing the reaction conditions, for example, a reaction carried out in water at 170 degrees C for 1 h with HBeta (Si/Al=19) and HUSY (Si/Al=15) catalysts gave yields of 62 and 56% for xylose and arabinose, respectively. With increased reaction time (6 h) and in presence of only water, HUSY resulted in yields of 30% xylose+arabinose and 18% furfural. However, in a biphasic reaction system (water+p-xylene, 170 degrees C, 6 h) yields of 56% furfural with 17% xylose+arabinose could be achieved. It was shown that with the addition of organic solvent the furfural yield could be increased from 18 to 56%. Under optimized reaction conditions, >90% carbon balance was observed. The study revealed that catalysts were recyclable with a 20% drop in activity for each subsequent run. It was observed that temperature, pressure, reaction time, substrate to catalyst ratio, solvent, and so forth had an effect on product formation. The catalysts were characterized by means of X-ray diffraction, temperature-programmed desorption of NH3, inductively coupled plasma spectroscopy, elemental analysis, and solid-state NMR (Si-29, Al-27) spectroscopy techniques.
Keywords: analytical methods; Biomass; carbohydrates; heterogeneous catalysis; zeolites

Synthesis of 2,5-furandicarboxylic acid by the aerobic oxidation of 5-hydroxymethyl furfural over supported metal catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Reaction Kinetics Mechanisms and Catalysis, 2014)
Supported Pt catalysts are synthesized, characterized and are used in the liquid phase air oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA). Under the optimum reaction conditions of a stepwise increase in the reaction temperature (75 and 140 degrees C for 12 h each), we achieved as high as 96 % FDCA yield in presence of 1 bar oxygen pressure over Pt/c-Al2O3. It is shown that as the oxygen pressure increases (1-10 bar), the FDCA yields decrease, since at higher partial pressure of oxygen, overoxidation reactions of substrate and product(s) are possible. It is interesting to note that even with air as an oxidant, we obtained similar yields of FDCA as that with oxygen. Moreover, the effects of base (weak or strong), its concentration (equimolar or excess) were studied in detail. It is important to increase the reaction temperature in a stepwise manner to achieve higher yields of FDCA since at higher temperatures HMF undergoes self-degradation and thus the yields of FDCA decrease. The self-degradation of HMF is also proved by undertaking the reaction under nitrogen environment. The study on the effect of substrate-to-catalyst ratio is done to improve up on the economics of overall process. The effect of supports (reducible and non-reducible) and their oxygen storage capacity is discussed and is proposed to be one of the factors to change the course of reaction. Furthermore, we have shown that FDCA formed in the reaction can be successfully isolated (91 %, isolated yield) in the pure form and its purity is confirmed by NMR, melting point, and elemental analysis. The catalysts were characterized with X-ray powder diffraction, transmission electron microscopy and inductively coupled plasma-optical emission spectroscopy techniques.
Keywords: Biomass; FDCA; green chemistry; heterogeneous catalyst; HMF; Impregnation; Oxidation